Studying the possibility of using Calcium Orthophosphate as a promising dental treatment of caries by analyzing the Infrared spectrum of inspected teeth samples - Alghoul, Abubaker Ali Yousif; Fayez, Tarek Mohamed; Ahssona, Marow Moftah Ali (Al-Mukhtar Journal of Sciences, 2022)
It is well known that Biomaterials play a significant role in the field of treatment of many dental diseases such as dental caries caused by bacteria. One of these significant biomaterials is calcium phosphate, formally known as hydroxyapatite. This study aims to investigate the effect of using hydroxyapatite on dental caries. In this research, some teeth samples infected by caries were studied experimentally. The collected teeth samples were taken from people of different age groups. After the chemical treatment of the teeth samples, at the laboratory, different percentages of calcium orthophosphate were added to each dental sample. Subsequently, these samples were subjected to spectroscopic analysis by infrared technique. The results showed the synthesis of new chemical bonds as a direct consequence of the interaction of calcium phosphate with the teeth tissue affected by dental caries. The absorption coefficients of the infrared, for different teeth samples, were at the following wavelengths: 2.93μm, 9.52μm, 0.1μm, 0.1μm. When comparing these wavelengths, the results show the formation of sharp peaks for dental samples treated with calcium phosphate. When identifying these peaks, the study showed that they form at small permeability coefficients compared to the permeability coefficients recorded for dental samples untreated with calcium phosphate.